2003
DOI: 10.1046/j.1365-2672.2003.02119.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid detection of Photobacterium damselae ssp. piscicida by a PCR technique and plating method

Abstract: Aims: To detect Photobacterium damselae ssp. piscicida using the PCR technique and plating method. Methods and Results: Two strains of P. damselae ssp. piscicida were isolated from cultured cobia (Rachycentron canadum) at two different fish farms in Taiwan. A pair of primers was designed to detect the capsular polysaccharide gene of P. damselae ssp. piscicida by PCR. Reference strains of different genus and different clinical strains were used for this study. The expected product (410 bp) was obtained from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
2
34
0
9
Order By: Relevance
“…piscicida strain O82352 was isolated from the kidney of yellowtail during an outbreak of pseudotuberculosis at a culture farm in Oita Prefecture, Japan, in 1998. The bacterium was identified using polymerase chain reaction (PCR) targeted at 16S ribosomal RNA and capsular polysaccharide [22,23]. The bacterium was precultured in 7 ml brain heart infusion (BHI) broth (Difco) supplemented with 1.5% NaCl (BHI) at 25°C with shaking at 100 rpm for 16 h. Then, 0.75 ml of the suspension was inoculated into 300 ml BHI broth, which was incubated at 25°C with shaking at 100 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…piscicida strain O82352 was isolated from the kidney of yellowtail during an outbreak of pseudotuberculosis at a culture farm in Oita Prefecture, Japan, in 1998. The bacterium was identified using polymerase chain reaction (PCR) targeted at 16S ribosomal RNA and capsular polysaccharide [22,23]. The bacterium was precultured in 7 ml brain heart infusion (BHI) broth (Difco) supplemented with 1.5% NaCl (BHI) at 25°C with shaking at 100 rpm for 16 h. Then, 0.75 ml of the suspension was inoculated into 300 ml BHI broth, which was incubated at 25°C with shaking at 100 rpm.…”
Section: Methodsmentioning
confidence: 99%
“…damselae, em especial nas seguintes características: ausência de atividade hemolítica em meio ágar sangue, e atividade negativa para redução do nitrato, urease, amilase e lípase (Romalde, 2002). Além disso, Rajan et al (2003) relataram ausência de crescimento em meio ágar tiossulfato citrato sais de bile sacarose (TCBS).…”
Section: Photobacterium Damselae Subsp Piscicidaunclassified
“…Nascimento et al (2014) também realizaram análises bacteriológicas, com base em fragmentos de órgãos internos, em 74 animais cultivados no Nordeste brasileiro, tendo obtido uma porcentagem de isolamento de 96% (71 peixes) de bactérias da família Vibrionaceae. Esses autores não relataram a presença de P. damselae, porém, utilizaram apenas ágar TCBS como meio de isolamento, o que restringiu a capacidade de isolar ambas as subespécies (Rajan et al, 2003;Korun & Timur, 2005). Ainda assim, Nascimento et al (2014) enfatizam que os exemplares de bijupirá analisados, embora aparentemente saudáveis, estão infectados com bactérias potencialmente patogênicas para peixes e humanos.…”
Section: Fotobacteriose No Brasilunclassified
See 1 more Smart Citation
“…A method based on duplex PCR of ureC and 16S rRNA genes was proposed by Osorio et al (2000), due to the lack of the ureC gene in the subspecies piscicida, but subspecies discrimination was based on indirect evidence (lack of amplification of ureC). Lately, a combined approach of PCR technique and plating method has been proposed (Rajan et al 2003). Other methods such as ribotyping (Magariños et al 1997), RAPD (Random Amplified Polymorphic DNA) (Magariños et al 2000), and amplified fragment length polymorphism (AFLP) (Thyssen et al 2000, Kvitt et al 2002 showed the ability to differentiate the 2 subspecies as well as to identify clusters of P. damselae subsp.…”
Section: Introductionmentioning
confidence: 99%